Observation on different strains of Aeromonas hydrophila from various diseased fishes - Nayak, K K; Mukherjee, S C; Das, B K (Indian Journal of Fisheries, 2011)
Aeromonas hydrophila was isolated and identified from a variety of disease spectra eg. eye disease, epizootic ulcerative disease syndrome, haemorrhagic septicaemia in carps, mullets, puntius and channa. Based on its biochemical properties, it was categorised into Kt, 1^, K, K4 and K5 respectively. Kj strain showed negative to esculin hydrolysis whereas IC, showed positive reaction to it. Kg showed positive reaction to lysine decarboxylase as others showed negative to it and K4 showed nonfermenting reaction to D-sucrose in comparison to other strains. K5 showed negative reaction to malonate as other four showed positive reaction.